2017
DOI: 10.1084/jem.20162040
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D at the Golgi controls NLRP3 inflammasome activation

Abstract: Zhang et al. show that Golgi-mediated protein kinase D (PKD) signaling is required and sufficient for NLRP3 inflammasome activation. PKD at the Golgi phosphorylates NLRP3 to release it from mitochondria-associated endoplasmic reticulum membranes, allowing for assembly of the mature inflammasome in the cytosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
232
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(257 citation statements)
references
References 74 publications
(117 reference statements)
20
232
1
4
Order By: Relevance
“…In agreement with our results, a recent study demonstrated that NLRP3 inflammasome agonists induce mitochondrial clustering around the Golgi, at which protein kinase D phosphorylates NLRP3 to promote assembly of the NLRP3 inflammasome (38). Additionally, the authors showed that disruption of Golgi integrity by BFA treatment blocks NLRP3 inflammasome activation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, a recent study demonstrated that NLRP3 inflammasome agonists induce mitochondrial clustering around the Golgi, at which protein kinase D phosphorylates NLRP3 to promote assembly of the NLRP3 inflammasome (38). Additionally, the authors showed that disruption of Golgi integrity by BFA treatment blocks NLRP3 inflammasome activation.…”
Section: Discussionsupporting
confidence: 93%
“…However, it remains elusive how NLRP3 is capable of sensing cytosolic alterations upon stimulation with diverse NLRP3activating agonists. Recent studies demonstrated that the intracellular organelle network might be important for the assembly of NLRP3 inflammasome, including the mitochondrial translocation into the perinuclear regions of macrophages upon NLRP3-activating stimulation (19,21,38). This mitochondria-specific spatial rearrangement might interact with ER to form mitochondriaassociated ER membranes, which could serve as a crucial platform for the formation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…Licensing of sensors for activation may include phosphorylation/dephosphorylation (NLRC4, NLRP3, Pyrin) and deubiquitination (NLRP3), while negative regulation is exemplified by the recruitment of the decoy Pyrin‐only protein Pop3 that binds to AIM2 and IFI16 to prevent the recruitment of ASC . Additionally, recent work has demonstrated that the sensor concentration can be regulated at the level of subcellular compartments . Expression levels of pro‐IL1β and pro‐IL18 seem to determine which cytokines are released upon inflammasome activation.…”
Section: Assembly and Regulation Of Asc Specksmentioning
confidence: 99%
“…35 Additionally, recent work has demonstrated that the sensor concentration can be regulated at the level of subcellular compartments. 36 Expression levels of pro-IL1β and pro-IL18 seem to determine which cytokines are released upon inflammasome activation.…”
Section: Assembly and Regulation Of Asc Specksmentioning
confidence: 99%
“…En particulier NEK7 (NIMA-related protein kinase 7), qui se lie à NLRP3, est nécessaire à l'assemblage de l'inflammasome auquel elle participe, mais son activité kinase n'est pas essentielle [42]. Très récemment, il a été montré que la phosphorylation de la sérine S295 de NLRP3 par les PKD (protein kinase D) 1-3, activées en aval de la PLC et du DAG (diacylglycérol) serait nécessaire à l'assemblage de l'inflammasome [43]. Les mutants S295A et S295E, qui miment respectivement les états déphosphorylé et phosphorylé de cette sérine, sont tous deux inactifs.…”
Section: Modifications Post-traductionnelles De L'inflammasome Nlrp3 unclassified